Computer-assisted analysis of cervical vertebral bone age using cephalometric radiographs in Brazilian subjects - Maria de Paula Caldas; Gláucia Maria Bovi Ambrosano; Francisco Haiter Neto (Sociedade Brasileira de Pesquisa Odontológica, 2010)
The aims of this study were to develop a computerized program for objectively evaluating skeletal maturation on cephalometric radiographs, and to apply the new method to Brazilian subjects. The samples were taken from the patient files of Oral Radiological Clinics from the North, Northeast, Midwest and South regions of the country. A total of 717 subjects aged 7.0 to 15.9 years who had lateral cephalometric radiographs and hand-wrist radiographs were selected. A cervical vertebral computerized analysis was created in the Radiocef Studio 2 computer software for digital cephalometric analysis, and cervical vertebral bone age was calculated using the formulas developed by Caldas et al.17 (2007). Hand-wrist bone age was evaluated by the TW3 method. Analysis of variance (ANOVA) and the Tukey test were used to compare cervical vertebral bone age, hand-wrist bone age and chronological age (P < 0.05). No significant difference was found between cervical vertebral bone age and chronological age in all regions studied. When analyzing bone age, it was possible to observe a statistically significant difference between cervical vertebral bone age and hand-wrist bone age for female and male subjects in the North and Northeast regions, as well as for male subjects in the Midwest region. No significant difference was observed between bone age and chronological age in all regions except for male subjects in the North and female subjects in the Northeast. Using cervical vertebral bone age, it might be possible to evaluate skeletal maturation in an objective manner using cephalometric radiographs.